TACHOMETRIC GAS METERS OPERATION FEATURES - HORZHYI, IGOR; PYSARETS, ANNA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Solving problems related to accurate metering of natural gas requires a comprehensive approach that includes the development and implementation of new technologies, as well as the improvement of existing metering instruments.For commercial gas metering, instruments based on various measurement methods are widely used. In this case, a special place is occupied by tachometric meters, namely: membrane, rotary and turbine. The features of using each meters type depending on operating conditions are considered.High accuracy, a wide range of measured flow rates and relatively low cost are characteristic features of rotary meters, which contributes to their use in both residential and industrial sectors.The aim of the work is to develop a method for calculating the sensitive element moment of inertia of a rotary gas meter. This is one of the especially important stages in the design of such instruments.The sensitive element moment of inertia significantly affects the dynamic characteristics performances of the instrument, sensitivity and starting torque. Therefore, determining the optimal relationship between the sensitive element geometric parameters and other measuring chamber characteristics is an extremely important issue when designing rotary gas meter.The authors proposed an algorithm for determining the moment of inertia of a figure-eight-shaped rotor, which assumes a conditional rotor division into separate geometric components such as shaft, tooth head and central part. This made it possible to determine the sensitive element moment of inertia as the sum of the moments of inertia of the individual components relative to the rotor rotation axis. Mathematical expressions for the moments of inertia of each component and the rotor as a whole were substantiated.Based on the developed methodology, an assessment of the inertia moment for a figure-eight-shaped rotor was carried out. The influence of changing the rotor wall thickness on the moment of inertia was investigated with other sensitive element geometric characteristics remaining unchanged.A prospect for further work is to study the influence of the sensitive element geometric parameters on the metrological performances of the rotary gas meter.
Keywords: gas; tachometric gas meters; rotary gas meter; design; sensitive element; moment of inertia